URGENSI MANAJEMEN PERPUSTAKAAN DALAM PENGUATAN MINAT BACA SISWA DI SDN MALAKA SARI 03 JAKARTA TIMUR - Atika Yuniarsih; Yohamintin; Suharjuddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe the urgency of library management in increasing students' reading interest at SDN Malaka Sari 03, East Jakarta. The background of this study is the low literacy culture in Indonesia, one of which can be addressed through optimizing the role of school libraries. The method used is a qualitative approach with data collection techniques in the form of observation, interviews, and documentation. The results of the study indicate that library management at SDN Malaka Sari 03 has been running well through effective planning, organization, implementation, and supervision. The strategies implemented include scheduling library visits, routine literacy activities, providing relevant book collections, and utilizing technology through the procurement of digital books. In addition, collaboration between librarians, teachers, and students also contributes to creating a comfortable and supportive library atmosphere. However, challenges remain, such as limited library collections and the need to improve infrastructure. In general, good library management has been proven to increase students' reading interest and strengthen literacy culture in elementary schools.